The Influence of Good Governance Principles on Satisfaction of Participants National Health Insurance - Puguh Ika Listyorini; Mutmainah Dwi Novian Martin (LPPM Universitas Duta Bangsa Surakarta, 2019)
Participant satisfaction is a subjective value for the quality of service provided. If the principles of good governance are applied well, service user satisfaction will be high. The purpose of this study is to determine the effect of the application of the principle of good governances to the satisfaction of National Health Insurance participants at the Office of the Social Security Administering Agency in Surakarta. The research method used is quantitative analytic with cross sectional approach, with a sample of 256 people, taken with a quota sampling technique. Data collected by questionnaire, then analyzed by univariate, bivariate, and multivariate analysis. The results showed that there are influences on the principles of openness, accountability, responsibility, inindependency, pre-accountability, participation, Fairnes and equality, and dynamic with participant satisfaction. Of all the principles, the most influential on participant satisfaction is the principle of Fairnes and equality. The conclusion of this study is that there is an influence of the application of the principle of good governances on the satisfaction of participants of the national health insurance.